MENINGKATKAN KETERAMPILAN SOSIAL ABK MELALUI METODE BERMAIN KOOPERATIF DI PAUD INKLUSI - Anindya Purnama (FKIP Unirow Tuban, 2017)
This research is motivated by the importance of developing social skills for children with special needs in order to be able to interact with others in socially acceptable ways and bring benefits for themselves and others. The purpose of the research is to develop the social skills of the children with special needs through the method of playing cooperatively in the ECD institutions that organize inclusive education. The research approach used is quantitative with quasi experimental research type with nonrandomized design pretest-posttest control group design. Methods of collecting social skills data using observational checklists and rating scales referring to the Guttman scale. ABK's social skills are measured using 5 (five) dimensions of Caldarella and Merrel that are relationships with peers, self-management, academic ability, compliance, and assertive behavior. Before the data analysis is done the validity test and relay test first. Test Validity based on judgment expert, while Test reliability using Cronbach's Alpha with SPSS 22.00. Analysis of previous social skill data should be tested for normality by using one sample kolmogorov-smirnov test and homogeneity test by conducting F test. Hypothesis testing is performed after the two data tests yield normal and homogeneous distributed data, then the data is analyzed by using independent sample t-test .